Konsep Waris Berdasarkan Gender Dan Keadilan Dalam Kitab Melayu Is’af Al Khaaid Karya Syekh Muhammad Syukri Unus Al-Banjari - Ali Mu’ammar (Interdisciplinary Explorations in Research Journal, 2024)
Abstract This research explores the concept of inheritance based on gender and justice as presented in the Malay manuscript "Is’af Al Khaaid" by Sheikh Muhammad Syukri Unus Al-Banjari. The manuscript serves as the focal point for analysis to comprehend Sheikh Muhammad Syukri Unus Al-Banjari's perspectives on inheritance, with a specific emphasis on gender aspects and principles of justice. Employing a qualitative approach, this study delves into an in-depth textual analysis of the manuscript to identify gender perspectives in inheritance and to understand how the concept of justice is reflected in the distribution of inherited property. The research aims to provide further insights into Islamic views, particularly in the context of inheritance, and its implications on gender justice within society. The conclusions and findings of this study are expected to contribute significantly to the discourse on Islam, inheritance law, and gender perspectives concerning justice. Keywords: inheritance, gender, justice Abstrak Penelitian ini menggali konsep waris berdasarkan gender dan keadilan yang terkandung dalam kitab Melayu "Is’af Al Khaaid" karya Syekh Muhammad Syukri Unus Al-Banjari. Kitab tersebut menjadi fokus analisis untuk memahami pandangan Syekh Muhammad Syukri Unus Al-Banjari terhadap pewarisan, dengan penekanan pada aspek gender dan prinsip keadilan. Studi ini menggunakan pendekatan kualitatif dengan menganalisis teks kitab secara mendalam untuk mengidentifikasi perspektif gender dalam pemberian waris dan memahami bagaimana konsep keadilan tercermin dalam pembagian harta waris. Hasil penelitian ini diharapkan dapat memberikan wawasan lebih lanjut tentang pandangan agama Islam, terutama dalam konteks waris, serta implikasinya terhadap keadilan gender di masyarakat. Kesimpulan dan temuan studi ini diharapkan dapat memberikan sumbangan signifikan terhadap diskursus keislaman, hukum waris, dan perspektif gender dalam konteks keadilan. Kata Kunci: waris, gender, keadilan